Effective Low-cost Energy Saving Strategies in Supermarkets: An UK Case Study - Acha,Izquierdo S; Mavromatidis,G; Caritte,V; Shah,N (2016)
Supermarket buildings are complex energy systems that require careful study to make sure they perform in asensible manner. The retail pressure of delivering stores in a short time makes engineering commissioningteams prone to mistakes and therefore, despite stores being newly built and carefully designed, theirsystems are not ideally set up; thus making the building underperform from day one. Consequently, energysavings are within easy reach if an effort is made to re-evaluate stores shortly after their opening date. Thispaper focuses on how adequate monitoring and good housekeeping can lead to effective energy savingstrategies for a better management of services such as lighting, refrigeration, heating and ventilation.Additionally, a focused effort in curtailing energy use in supermarkets can also seriously reduce operationalcarbon related emissions; an ever-growing concern for retailers in an environment where sustainabilitypractice is highly valued by consumers. A case study of a 35,000 ft2 supermarket located in the south-eastof England serves as a vehicle to present and quantify effective, low-cost energy saving strategies.Extensive monitoring capabilities allow us to set a benchmark for all systems which then serves to assessthe effectiveness of trials performed. Trials consist of: a) enhancing the dimming capabilities of the lightingsystem by improving sensor location and code, b) improving settings of fans and boiler system that reduceheating and ventilation requirements, and c) advocating the proper use of night-blinds in cabinets coupledwith suction optimization of compressors that save energy use in the refrigeration system. All of these livetrials have the feature of working closely with store staff and management, specialised contractors andacademics. The synergy of parties allows the energy trials to succeed since aside from having solid technicalfoundations they have the full support from the people that work day in and day out in the supermarket &nda